2021-2022 Quick Reference Guide to Citrus Insecticides and Miticides: ENY-854/IN807, rev. 10/2021 - Diepenbrock, L. M.; Stelinski, L. L.; Burrow, J. D.; Qureshi, J. A. (EDIS, 2021)
A two-page quick reference guide to citrus insecticides and miticides recommended in the Florida Citrus Pest Management Guide, their effects on important citrus pests, and their natural enemies.